In-Vitro Rooting Induction On The Embryo Somatic Of Dendrobium Species From Riau Province Indonesia - Pebra Heriansyah; Hasan Basri Jumin; Maizar Maizar (Paspalum: Jurnal Ilmiah Pertanian, 2020)
Rooting induction is a very important stage in in-vitro for the anticipation of the extinction, In this paper, the rooting induction of embryo somatic dendrobium species from Riau Province Indonesia is studied using different sucrose concentrations (0 g L-1; 25 g L-1; 50 g L-1; 75 g L-1), and Kinetin (0 mg L-1; 0,1 mg L-1; 1,0 mg L-1; 10 mg L-1), in a modified MS medium containing half the regular concentration of macronutrients at pH 5.6, with 50 g L-1 sucrose and 1,0 mg L-1  kinetin was optimal for a percentage of explant producing root, a number of roots, root high, root and shoot ratio  (T/R Ratio).